Evaluation of Information Technology Governance in the ICT Unit of Sari Mulia University Using COBIT 5: EDM02 and APO07 - Suraya Akbar; Alberto David Halomoan Sitorus; Muhammad Rama Alfiannur; Ratna Lindawati (LPPM Universitas Sari Mulia, 2025)
Information technology (IT) is a crucial element in digital transformation in higher education. Effective IT governance is critical to aligning technology strategy with organizational goals. This research aims to instill a level of IT governance maturity in the ICT Unit of Sari Mulia University (UNISM) using the COBIT 5 framework, with a focus on the EDM02 (Ensure Benefits Delivery) and APO07 (Manage Human Resources) domains. The research method used is a qualitative approach by collecting data through surveys and direct interviews with the UNISM ICT team. The analysis is carried out by measuring the current level of maturity, determining the expected level of maturity, and conducting a gap analysis. The evaluation results show that the EDM02 domain reached a maturity level of Level 3 (Established) with an average score of 2.66. Meanwhile, the APO07 domain is at Level 1 (Performed) with a score of 1.16. The average gap analysis of the two domains is 3.09, with the expected target being Level 5 (Optimizing). This research concludes that there is a significant imbalance between the current and expected conditions of IT governance. Recommendations are given to implement standard processes consistently and make continuous improvements to support the achievement of UNISM's strategic goals.